Learning with the city via enchantment: photo-walks as creative encounters. Issue 1 (2nd January 2016) - Pyyry, Noora
Abstract : In this paper, I approach learning as a process of rethinking the world that happens via the surprising experience of "enchantment." This process becomes possible by dwelling, that is, by forming meaningful multisensory engagements with one's surroundings. I present my arguments by discussing photo-walks that students conducted in Helsinki as part of a geography-learning project. During the photo-walks, learning happened with the spaces of hanging out. In contrast to common understandings of learning, this learning with the city is non-instrumental: it is making the familiar unfamiliar by paying attention to the particular in everyday spaces. Methods such as photography are understood as creative encounters that can help in re-cognizing the world and fostering one's ethical sensitivity.